Covid-19 In A Patient With Pemphigus: A Case Report - Dwizella, Nandya; Pratama, Nevristia (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Pemphigus disease, especsially Pemphigus Vulgaris (PV), is an autoimmune disease resulting in blisters on the skin and mucosa due to autoantibodies attacking desmogleins (DSG) 1 and 3. Autoimmunity development in PV may be idiopathic or induced by neoplasms, drugs, infections, or inflammatory processes. Besides affecting the respiratory tract, COVID-19 may also affect other systems, such as the skin. The pathogenesis of autoimmune diseases and COVID-19 have similarities, which is an overreaction of the immune system. Purpose: To report a case about the association between PV autoimmune disease and COVID-19. Case: A 30-year-old woman presented with full-body pain and ulcers. Three days before the skin lesions, the patient complained of a mild cough, and the SARS-CoV-2 examination was positive. The patient was treated with systemic and topical corticosteroids along with broad-spectrum antivirals. The patient was discharged with an improved lesion condition and a negative SARS-CoV-2 PCR on day 5 of treatment. Discussion: Prolonged viral infection or viral infection itself, such as COVID-19 can cause immune system dysregulation leading to autoimmune skin lesions with different mechanisms. The use of corticosteroids or immunosuppressants in autoimmune diseases increases the risk of COVID-19 infection in a pandemic. Conclusion: In the COVID-19 pandemic, COVID-19 and autoimmune diseases such as pemphigus vulgaris are interrelated with the presence of immune dysregulation leading to skin lesions